The somatic experiencing of therapists when working with clients who are living with trauma: An exploration using collage - Baker, Helene (2020)
The bodily experiencing of the therapist is a constant presence in the therapeutic space. Person-centred theory and practice is all about the organism, and literature on working with trauma has shown the fundamental significance of the client's body in traumatic experiencing and healing. The physical body of the therapist, however, is largely absent from the literature. This study aims to explore the bodily experiencing of the therapist when working with clients who are living with trauma. In this context, 'bodily experiencing' describes the physical expression of the therapist as a living, sensing and responding being, and includes bodily relationship to self, others and the world around.